If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(y + 5) = 15 Reorder the terms: -3(5 + y) = 15 (5 * -3 + y * -3) = 15 (-15 + -3y) = 15 Solving -15 + -3y = 15 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + -3y = 15 + 15 Combine like terms: -15 + 15 = 0 0 + -3y = 15 + 15 -3y = 15 + 15 Combine like terms: 15 + 15 = 30 -3y = 30 Divide each side by '-3'. y = -10 Simplifying y = -10
| 2overs-7=11 | | -9=-4(u-18)+-5 | | 6x3/6 | | 13+2p=-5-6p | | 0.09xX=110.30 | | X+(x-1)=2(x+3) | | 12x-2m= | | 3x4/9= | | -5x+2(4x-15)=-63 | | -3(-7w+4)-3w=4(w-5)-4 | | W=1000-0.2t | | 28a^3b^4+20a^2b^2-16ab^3= | | x^8=140 | | 40x-40=28 | | 67+4y-30=15y-12-4y | | 9+3y-3=7y+15-3y | | 8x+3y=67 | | 8x-5y=-9 | | 18+-9= | | V(w-l)=p | | 93-(7x+6)=7(x+6)+x | | 2x^2+14x+59=0 | | Ab+c=2 | | 0=p-20/-2 | | 8x+9y-(2x+y)= | | log(x)+8.75=0 | | -2(6x-7)+6x=5+2(2x-3) | | j+16=-10-j | | 20sinx=10 | | 10x+9-9x-15= | | 4n-40=7(-2nt+2) | | 4/100= |